2019
DOI: 10.1002/ijc.32560
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic elongation factor 2 kinase promotes angiogenesis in hepatocellular carcinoma via PI3K/Akt and STAT3

Abstract: Hepatocellular carcinoma (HCC) is an aggressive malignancy with increasing mortality in China. Angiogenesis is crucial for tumor formation, development and metastasis in HCC. Previous studies indicated that high expression levels of elongation factor 2 kinase (eEF2K), a protein kinase that negatively regulates the elongation stage of translation, were associated with poor prognosis of HCC. Here, we show that pharmacological inhibition or knockdown of eEF2K in highly metastatic liver cancer cells inhibits their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…Taken together with the roles of eEF2K in promoting the survival of cancer cells under nutrientdeprived conditions [6,35,36], in cell migration and cancer cell metastasis [9], and in angiogenesis [10], our present data add further support to the conclusion that disabling eEF2K may be a valuable therapeutic approach to tackling established solid tumours, at least for some types of cancers. However, as is the case with targeting other processes such as autophagy and mTORC1 signaling [2,45,46], in some specific settings the inhibition of eEF2K may actually promote cancer-related processes, e.g., tumour initiation.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Taken together with the roles of eEF2K in promoting the survival of cancer cells under nutrientdeprived conditions [6,35,36], in cell migration and cancer cell metastasis [9], and in angiogenesis [10], our present data add further support to the conclusion that disabling eEF2K may be a valuable therapeutic approach to tackling established solid tumours, at least for some types of cancers. However, as is the case with targeting other processes such as autophagy and mTORC1 signaling [2,45,46], in some specific settings the inhibition of eEF2K may actually promote cancer-related processes, e.g., tumour initiation.…”
Section: Discussionsupporting
confidence: 77%
“…Here we show that eEF2K positively regulates the levels of the major immune checkpoint protein, PD-L1 in three different types of cancer cells (A549, PC3 and MDA-MB-231) and provide evidence that this occurs at the level of the translation of its mRNA. This adds to the growing evidence that eEF2K helps to promote tumour growth and metastasis, providing further impetus to the concept that eEF2K (a non-essential and atypical protein kinase) is an attractive target for the therapy of at least some types of solid tumours [8][9][10]37]. eEF2K is activated under conditions which occur within tumours, such as nutrient depletion [6] or hypoxia [25]; this will also facilitate the production of PD-L1 and thus enhance the tumour's resistance to immune attack.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, eEF2K plays role in tumour cell survival during nutrient depletion, probably by slowing down protein synthesis and thereby reducing the consumption of energy and amino acids [6][7][8] and in cancer cell migration and angiogenesis, by regulating the synthesis of proteins involved in this process including some integrins [9,10]. Indeed, a number of studies have shown that eEF2K activity and/or alteration of translation elongation rates affects the translation of specific mRNAs and thus the synthesis of individual types of proteins (e.g., [9,11,12]), although the mechanisms underlying this have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis, an important feature of cancer, was induced early during the multistage development of cancers 22,23 . High levels of angiogenesis related factors are signi cantly associated with rapid cancer recurrence and poorly survival 24,25 . Blocking synthesis and secretion of these growth factors would greatly impair tumor cell proliferation, metastasis and angiogenesis [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%